1997
DOI: 10.3109/10715769709097801
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Spectroscopic Investigations of Salivary Antioxidant Consumption by an Oral Rinse Preparation Containing the Stable Free Radical Species Chlorine Dioxide (CIO2)

Abstract: A multicomponent evaluation of the oxidative consumption of salivary biomolecules by a commercially-available oral rinse preparation containing an admixture of the stable free radical species chlorine dioxide (ClO2.) with chlorite anion (ClO2-) has been investigated using high resolution 1H NMR spectroscopy. The results obtained demonstrated that ClO2. and/or ClO2- present in this preparation effected the oxidative decarboxylation of salivary pyruvate (to acetate and CO2). Experiments conducted on chemical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 19 publications
1
39
0
1
Order By: Relevance
“…Other features of the spectra obtained are signals attributable to trimethylamine oxide (s, = 3.27 ppm), a metabolite presumably derived from the trimethylamine oxidase-mediated oxidation of dietary trimethylamine (s, = 2.97 ppm), the a-and b-anomers of glucose (sugar ring proton multiplets in the 3.25-4.00 ppm region) and the a-anomeric proton (d, = 5.26 ppm). Moreover, methanol (s, = 3.38 ppm), a product presumably arising from the direct or passive inhalation of cigarette smoke (via combustion of tobacco lignin) 25 was also detectable in many of the samples collected. All signals detectable in 600 MHz 1 H-NMR spectra acquired on post-neutralized HClO 4 extracts of primary root carious lesions are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Other features of the spectra obtained are signals attributable to trimethylamine oxide (s, = 3.27 ppm), a metabolite presumably derived from the trimethylamine oxidase-mediated oxidation of dietary trimethylamine (s, = 2.97 ppm), the a-and b-anomers of glucose (sugar ring proton multiplets in the 3.25-4.00 ppm region) and the a-anomeric proton (d, = 5.26 ppm). Moreover, methanol (s, = 3.38 ppm), a product presumably arising from the direct or passive inhalation of cigarette smoke (via combustion of tobacco lignin) 25 was also detectable in many of the samples collected. All signals detectable in 600 MHz 1 H-NMR spectra acquired on post-neutralized HClO 4 extracts of primary root carious lesions are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 Previous studies have suggested that ClO 2 and chlorite anion are powerful bactericidal agents to most of the periodontogenic microorganisms. [23][24][25] It was also shown to be effective in treating halitosis, plaque, and gingivitis. 26,27 Owing to minimal adverse effects of these newer materials when compared to clinical gold standard (chlorhexidine), it is worthwhile to evaluate the effectiveness of these agents among patients undergoing fixed orthodontic treatment.…”
mentioning
confidence: 99%
“…Cysteine and methionine oxidizing agent [76], antimicrobial [77] Mouthwash [75], dentifrice [80], mouthspray [81,82], chewing gum [83] Dehydroascorbic acid Amino acid containing sulphur oxidizing agent [86] Dentifrice [86] Essential oils Antimicrobial [88], antiseptic and anticaries [92] Mouthwash [87,91], mouthspray [91], dentifrice [91,92] Antimicrobial [110,116,117] Mouthrinse [65,79,113,117], dentifrice [112,113,116], chewing gum [117] Activated carbon Odorant absorber [120] Dentifrince, chewing gum, scraper [120] Enzyme…”
Section: Zinc Saltsmentioning
confidence: 99%